Motor Coordination and Psychosocial Correlates in a Normative Adolescent Sample - Rigoli, Daniela; Piek, Jan; Kane, Robert (American Academy of Pediatrics, 2012)
OBJECTIVES: Previous research has revealed an important relationship between motor coordination difficulties and internalizing problems such as anxiety and depressive symptoms. However, further research is needed to understand the potential mediating factors in this relationship. The aim of the current study was to examine whether the association between motor coordination and emotional functioning is mediated by self-perceptions in a normative sample of adolescents. METHODS: Participants included 93 adolescents aged 12 to 16 years. The Movement Assessment Battery for Children–2 provided 2 indicators of motor coordination; the Mood and Feelings Questionnaire and Spence Children’s Anxiety Scale provided 2 indicators of emotional functioning; and the Self-Description Questionnaire–II provided 6 indicators for self-perceived competence. RESULTS: Structural equation modeling revealed that motor coordination affects emotional functioning via self-perceptions. CONCLUSIONS: These results suggest that the relationship between motor coordination and emotional functioning in adolescents from a normative sample may be understood in terms of a mechanism by which motor coordination has an indirect impact on emotional outcomes through various self-perception domains. These findings have important implications for increasing awareness and developing appropriate treatment programs for motor coordination and emotional difficulties.